2016
DOI: 10.1111/dmcn.13116
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics in cerebral palsy subtypes: a comparative assessment

Abstract: Our study reveals differences in growth rates between hemiplegic, diplegic, and quadriplegic CP subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
(102 reference statements)
3
11
0
1
Order By: Relevance
“…Another limitation is the absence of ‘mixed’ as a CP subtype for children with both dyskinetic and spastic features. Similarly, in another related paper Stanek et al demonstrated that the growth of patients with quadriplegic CP was consistently lower than patients with diplegic or hemiplegic CP. This paper did not differentiate children by CP subtype.…”
mentioning
confidence: 83%
“…Another limitation is the absence of ‘mixed’ as a CP subtype for children with both dyskinetic and spastic features. Similarly, in another related paper Stanek et al demonstrated that the growth of patients with quadriplegic CP was consistently lower than patients with diplegic or hemiplegic CP. This paper did not differentiate children by CP subtype.…”
mentioning
confidence: 83%
“…This diagnosis can potentially be inaccurate if other factors like disease activity or clinical progression are not considered. Malnutrition has several impacts on disabled individuals but misdiagnosis of failure to thrive is consequential [21,22].…”
Section: Classifications Of Cerebral Palsy and Their Effects On The Qmentioning
confidence: 99%
“…Patients with cerebral palsy are seen to grow at a slower rate when compared to typical developmental milestones even in the presence of optimum healthcare and nutrition [22]. This could be perceived by the caretaker as them not doing enough and initiating unwarranted adjuvant feeding therapy.…”
Section: Classifications Of Cerebral Palsy and Their Effects On The Qmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not detect significant difference between functionality, CP type and body weight, height and BMI Z-scores in CP patients. beslenme problemleri olarak sırasıyla %6 3. gastroözofageal reflü, %14.6 yutma güçlüğü, %33.3 salya akıtma ve % 68.8 diş problemi tespit edildi.…”
unclassified